2017
DOI: 10.1002/ppul.23886
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme insertion/deletion gene polymorphism in Egyptian children with CAP: A case‐control study

Abstract: The ACE I/D polymorphism (rs4340) may contribute to the genetic susceptibility of CAP in Egyptian children. The ACE D allele and DD genotype were associated with higher serum ACE levels among studied CAP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In an interesting case-control study, it was reported that the angiotensin converting enzyme polymorphism rs4340 was associated with increased risk for CAP in Egyptian children. 48…”
Section: Respiratory Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an interesting case-control study, it was reported that the angiotensin converting enzyme polymorphism rs4340 was associated with increased risk for CAP in Egyptian children. 48…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…Genetic factors may affect susceptibility to CAP. In an interesting case‐control study, it was reported that the angiotensin converting enzyme polymorphism rs4340 was associated with increased risk for CAP in Egyptian children . Erlichman et al in Israel reported a retrospective analysis of 144 hospitalized patients over a 10‐year period, with CAP complicated by necrotizing pneumonia, empyema, or parapneumonic effusion .…”
Section: Introductionmentioning
confidence: 99%